Dalits in India : strategies for inclusive development - National Seminar on "Impoverishment Among Dalits in India: Strategies for Inclusive Development" (2014 : Centre for Study of Social Exclusion and Inclusive Policy, Andhra University); Subha Rao, P. (Visakhapatnam : Uday Publishing House, 2017)
Papers presented at the National Seminar on "Impoverishment among Dalits in India: Strategies for Inclusive Development", held at Centre for Study of Social Exclusion and Inclusive Policy, Andhra University, Visakhapatnam, Andhra Pradesh, during 21st and 22nd March 2014, sponsored by Indian Council of Social Science Research, New Delhi.
Includes index
Keywords: Dalits -- India -- Social conditions -- Congresses; Dalits -- Government policy -- India -- Congresses; India